2017
DOI: 10.7759/cureus.961
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Prostate Cancer-Specific Mortality for High-Risk Prostate Cancer: A Population-Based Study

Abstract: IntroductionRace may be a significant factor that influences prostate cancer (PCa) survival, with the Asian (AsA) race being associated with better outcomes compared to African American (AA) and Non-Hispanic Whites (NHW). This study evaluates race-dependent variation in PCa-specific mortality (PCSM) associated with radiation dose-escalation exemplified by external beam radiotherapy (EBRT) with a brachytherapy (BT) boost in Gleason score 8-10 PCa.Methods28,956 men diagnosed with clinically localized PCa and Gle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Our study preserve the trend observed in various studies which have shown significant race disparities in PCa with AAM enduring the worst survival outcome [13,17,[30][31][32][33]. Using a similar approach to account for competing risk, a recent study by Wang et al [17] reported high risk of PCSM among AAM. In another study by Tyson et al, authors reported significantly worse survival among AAM compared to white men [30].…”
Section: Discussionsupporting
confidence: 86%
“…Our study preserve the trend observed in various studies which have shown significant race disparities in PCa with AAM enduring the worst survival outcome [13,17,[30][31][32][33]. Using a similar approach to account for competing risk, a recent study by Wang et al [17] reported high risk of PCSM among AAM. In another study by Tyson et al, authors reported significantly worse survival among AAM compared to white men [30].…”
Section: Discussionsupporting
confidence: 86%
“…This discrepancy between the results of our study and that of others may be due to biological and racial differences. Previous studies have also indicated that there may be racial differences in the treatment response of certain cancers to radiotherapy . In addition, our results showed that higher radiation doses (>4,000 cGy) were more likely to achieve a complete response compared with lower radiation doses (≤4,000 cGy).…”
Section: Discussionsupporting
confidence: 74%
“…Prostate cancer survival among American men has improved over recent decades; however, it remains the most common cancer in all races, the second leading cause of cancer death in Whites, Blacks, and Hispanic men, and the fourth leading cause of cancer death in Asian Americans and Pacific Islanders (AAPIs) in the United States 1 . Racial disparities in prostate cancer survival are well documented 2‐9 . Black men not only have a higher incidence rate of prostate cancer but also are more than twice as likely to die of the disease in comparison with White men 10‐12 .…”
Section: Introductionmentioning
confidence: 99%